Sustainable Livelihood Security of Integrated Farming Systems Practicing Farmers through Different Enterprise Combinations in Andhra Pradesh (Indian Journal of Extension Education, 2022)
The present study described the sustainable livelihood security of integrated farming systems practicing 189 farmers through different enterprise combinations in Chittoor district of Rayalaseema region, East Godavari from Coastal region and Srikakulam from North Coastal region during 2020-21. Indicators under each dimension of sustainable livelihood security were selected by item analysis. Out of 52 indicators, finally 25 indicators of sustainable livelihood security were selected based on relevancy weightage and mean relevancy score. The results revealed that majority of the farmers practicing Integrated Farming System had permanent asset creation (54.50%), food and nutritional security (53.97%), economic security (53.97%), input recycling (52.38%), occupational security (51.32%), financial security (50.79%), environmental security (47.09%) and social security (42.33%). The overall sustainable livelihood security index was nearly half (47.62%) among the farmers in medium category. Most of the farmers were having medium and high sustainable livelihood security due to integration of more enterprises which enabled optimum utilization of available resources through recycling resulting in more income, employment, and more food security throughout the year.